2007
DOI: 10.1099/vir.0.83171-0
|View full text |Cite
|
Sign up to set email alerts
|

Functional interaction of the human cytomegalovirus IE2 protein with histone deacetylase 2 in infected human fibroblasts

Abstract: In human cytomegalovirus (HCMV)-infected cells, the 86 kDa immediate-early (IE) 2 protein plays a key role in transactivating downstream viral genes. Recently, IE2 has been shown to interact with histone deacetylase 1 (HDAC1) and HDAC3. HDAC1 recruited by IE2 was required for IE2-mediated autorepression of the major IE (MIE) promoter, whereas IE2-HDAC3 interaction was suggested to relieve the repressive effect of HDAC3 on viral early promoters. However, whether IE2 indeed inhibits HDAC's deacetylation activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 26 publications
(32 reference statements)
5
53
0
1
Order By: Relevance
“…Park et al (36) have reported that total HDAC2 deacetylase activity decreases early during HCMV infection. We were interested in determining the impact of pUL97 kinase activity on deacetylase activity in the presence and absence of infection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Park et al (36) have reported that total HDAC2 deacetylase activity decreases early during HCMV infection. We were interested in determining the impact of pUL97 kinase activity on deacetylase activity in the presence and absence of infection.…”
Section: Resultsmentioning
confidence: 99%
“…DAXX interacts with HDAC1, and together they repress transcription (33). Also, the HCMV pUL123 (IE1) protein inhibits histone deacetylation (34) and, along with pUL122 (IE2), has been shown to affect the repressive actions of HDAC1, 2, and 3 (34)(35)(36)(37). Other HCMV proteins interact with HDACs or HDACcontaining complexes, including pUL29/28, which associates with the nucleosome remodeling and deacetylase complex, NuRD, influencing both viral (25) and cellular gene expression (38).…”
mentioning
confidence: 99%
“…Late promoters remain largely associated with repressive chromatin marks and only begin to become acetylated starting at 24 hpi (6,16). Binding of IE2-86 to HDACs 1, 2, and 3 and multiple histone methyltransferases (HMTs) during the late stages of infection may activate transcription from late promoters (37,40,46). However, it is also possible that IE2-86 transactivates late promoters through its interactions with many other viral and cellular partners or that the late-accumulating IE2-86 is responsible for one of the many other functions attributed to this protein (65).…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that viral proteins target HDACs and may modulate viral and cellular gene expression (Reeves et al, 2006;SoderbergNaucier, 2006;Park et al, 2007c;Mehta et al, 2009).…”
Section: Human Cytomegalovirus and Hhv-5mentioning
confidence: 99%